A mineral-based composite soil amendment and method of making same

CN122563602BActive Publication Date: 2026-10-30LIAONING QUANMINKANG BIOLOGICAL ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611071232.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-30
Estimated Expiration
2046-07-20

AI Technical Summary

Technical Problem

然而,传统无机改良剂存在明显的局限性:石灰类材料长期施用易导致土壤板结、养分不平衡和次生盐渍化;石膏类材料改良效果单一,且可能引入有害杂质;工业废弃物基改良剂则存在成分不稳定、重金属含量超标等环境风险

Benefits of technology

[0023]1、本发明通过白云石酸洗除杂、硅烷偶联剂表面活化、多官能团单体原位共聚的分步改性工艺,构建了白云石内核-硅烷过渡层-共聚物外壳的三层核壳有机-无机杂化结构。通过共价键实现无机矿物与有机组分的牢固结合,在土壤水环境冲刷、干湿交替等自然条件下不易发生分层或脱落,有助于延缓改良效果的衰减,延长产品的有效作用周期。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of soil improver, and more particularly to a mineral-based composite soil improver and a preparation method thereof, which comprises the following steps: firstly, crushing and screening dolomite, removing impurities by hydrochloric acid pickling, washing to neutral and drying to obtain pretreated powder; then, placing the powder in an acidic ethanol solution, adding a silane coupling agent to hydrolyze and condense to obtain activated dolomite; under the protection of inert gas, adding three functional monomers and an initiator to the water phase to copolymerize, and obtaining modified dolomite after refining; finally, mixing the modified dolomite with attapulgite, adding a composite microbial agent, adjusting humidity, granulating and drying at low temperature to obtain the finished product. The present application can passivate heavy metals in soil, fix nutrients, optimize soil aggregate structure, and maintain the activity of beneficial microorganisms, thereby comprehensively treating acidified and damaged soil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of soil conditioner technology, and in particular to a mineral-based composite soil conditioner and its preparation method. Background Technology

[0002] Soil conditioners, also known as soil amendments, are used to improve the physical properties of soil. Existing soil conditioners are mainly classified into inorganic, organic, biological, and composite types. Among them, inorganic conditioners, represented by lime, gypsum, and phosphogypsum, have advantages such as readily available raw materials, low cost, and rapid effects, making them the most widely used soil amendment materials. However, traditional inorganic conditioners have significant limitations: long-term application of lime-based materials can easily lead to soil compaction, nutrient imbalance, and secondary salinization; gypsum-based materials have limited improvement effects and may introduce harmful impurities; and industrial waste-based conditioners pose environmental risks such as unstable composition and excessive heavy metal content. Organic conditioners, such as livestock and poultry manure, crop straw, and biochar, can increase soil organic matter content, improve soil aggregate structure, enhance soil water and fertilizer retention capacity, and provide carbon and energy sources for soil microorganisms, promoting the healthy development of soil microbial communities. However, organic soil conditioners also have drawbacks such as low nutrient content, slow decomposition rate, and long improvement cycle. Furthermore, some organic materials may carry pathogens, parasite eggs, and heavy metals, posing a risk of secondary pollution. Biological soil conditioners mainly include microbial agents and plant extracts, which can activate soil nutrients and inhibit soil-borne diseases through the life activities of microorganisms. However, biological agents are sensitive to environmental conditions, have difficulty colonizing the soil, and their effectiveness is unstable.

[0003] To address the limited effectiveness and singular function of single soil conditioners, composite soil conditioners have become a research hotspot in recent years. Among them, mineral-based composite soil conditioners use natural minerals as the main raw material, combining them with organic materials, biological agents, or other functional materials to fully leverage the synergistic effects of each component, achieving comprehensive improvement of soil's physicochemical and biological properties. This has led to the development of various mineral-biochar, mineral-humic acid, and mineral-microorganism composite systems. For example, patent publication number CN106281353A discloses a mineral soil conditioner and its preparation method, including: mixing and grinding perlite, zeolite, sepiolite, vermiculite, and bentonite; then adding hydroxypropyl cellulose, polyacrylamide, humic acid, lignin, phosphorus pentoxide, and a chelating agent, followed by drying to obtain the mineral soil conditioner. This soil conditioner can increase the organic matter and nutrient content in the soil, loosen compacted soil, and promote plant growth.

[0004] However, most existing mineral-based composite soil conditioners employ simple physical mixing processes, resulting in a lack of effective chemical bonds between inorganic minerals and organic components. This leads to weak interfacial adhesion, making the organic components easily leached away in water-rich soil environments, causing a rapid decline in the conditioner's effectiveness and poor long-term sustainability. Furthermore, natural minerals, lacking surface activation modification, have few surface active sites and limited ion exchange capacity and adsorption capacity. Passivation of heavy metal ions in the soil relies primarily on physical adsorption, resulting in weak binding forces. When soil pH fluctuates, heavy metals are easily desorbed and reactivated, posing a risk of secondary pollution. Summary of the Invention

[0005] To address the problems mentioned in the background section, this invention provides a mineral-based composite soil conditioner and its preparation method.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing a mineral-based composite soil conditioner includes the following steps:

[0008] S1. After crushing and sieving the dolomite, it is acid-washed with hydrochloric acid solution to remove impurities for 1-3 hours. The solid-liquid ratio is 1:(5-10)g / mL. After washing until neutral, it is dried to obtain pretreated dolomite powder.

[0009] S2. Disperse the pretreated dolomite powder in an acidic ethanol aqueous solution with a solid-liquid ratio of 1:(8-12)g / mL, stir and disperse for 15-30min, add γ-methacryloxypropyltrimethoxysilane to carry out hydrolysis and condensation reaction to obtain activated dolomite.

[0010] S3. Under inert gas protection, the activated dolomite is dispersed in water at a solid-liquid ratio of 1:(10-15)g / mL. The mixture is stirred and dispersed for 20-40 min. Ethyl methacrylate, sodium vinyl sulfonate, N-(2-hydroxyethyl)acrylamide and an initiator are added to carry out a copolymerization reaction. The product is washed, dried and ground to obtain modified dolomite.

[0011] S4. Dry mix the modified dolomite and attapulgite powder evenly for 10-20 minutes at a stirring speed of 100-200 rpm. Then add the compound microbial agent and mix for 5-10 minutes at a stirring speed of 50-100 rpm. Adjust the humidity to 15-25% and granulate. Dry at low temperature to obtain the finished product.

[0012] Further, in step S1, the concentration of the hydrochloric acid solution is 0.05-0.2 mol / L; after pulverization, it is passed through a 100-200 mesh sieve, the drying temperature is 80-105℃, and the drying time is 4-8h.

[0013] Furthermore, in step S2, the pH of the acidic ethanol aqueous solution is adjusted to 3.5-4.5 using glacial acetic acid, and the ethanol volume fraction is 80-95%.

[0014] Furthermore, in step S2, the amount of γ-methacryloxypropyltrimethoxysilane used is 2-5% of the mass of the pretreated dolomite powder, the temperature of the hydrolysis-condensation reaction is 55-65℃, the reaction time is 2-4h, and the stirring speed during the reaction is 150-250rpm.

[0015] Further, in step S3, the initiator is selected from ammonium persulfate or potassium persulfate; the amount of initiator is 0.5-1.5% of the total mass of ethyl methacrylate, sodium vinyl sulfonate and N-(2-hydroxyethyl)acrylamide; the mass ratio of ethyl methacrylate, sodium vinyl sulfonate and N-(2-hydroxyethyl)acrylamide is (3.8-4.2):(1.9-2.1):(2.8-3.2).

[0016] Furthermore, the temperature of the copolymerization reaction in step S3 is 65-75℃, the reaction time is 3-5h, and nitrogen or argon is continuously introduced as an inert gas during the reaction, with a gas flow rate of 50-100mL / min.

[0017] Furthermore, in step S4, the compound microbial agent is prepared by mixing Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosa in a viable count ratio of (2-4):(1-3):1, with a total viable count of not less than 2.0 × 10⁻⁶. 9 CFU / g.

[0018] Furthermore, in step S4, a disc granulator is used for granulation, and the rotation speed of the disc is controlled at 25-35 rpm to produce spherical particles with a particle size of 2-4 mm.

[0019] Furthermore, in step S4, the low-temperature drying is carried out using a fluidized bed dryer, with the drying temperature controlled at 40-55℃ and the drying time at 2-4 hours, so that the final moisture content of the particles is reduced to below 8%.

[0020] According to another aspect of the present invention, a mineral-based composite soil conditioner prepared by the above-described preparation method is provided, which is prepared from the following raw materials in parts by weight:

[0021] Modified dolomite 65-80 parts, attapulgite powder 20-30 parts, compound microbial agent 0.5-2.0 parts; the attapulgite powder is natural attapulgite raw ore powder that has passed through a 200-300 mesh sieve.

[0022] The beneficial effects of this invention are:

[0023] 1. This invention utilizes a stepwise modification process involving dolomite acid washing for impurity removal, silane coupling agent surface activation, and in-situ copolymerization of multifunctional monomers to construct a three-layer core-shell organic-inorganic hybrid structure: a dolomite core, a silane transition layer, and a copolymer shell. Covalent bonds achieve a strong bond between the inorganic minerals and organic components, making it less prone to delamination or detachment under natural conditions such as soil water erosion and alternating wet and dry conditions. This helps to delay the decay of the modification effect and extend the effective lifespan of the product.

[0024] 2. This invention features a three-dimensional network copolymer functional layer grown in situ on the surface of dolomite, uniformly distributed with various functional groups such as phosphoric acid, sulfonic acid, hydroxyl, and amide groups. Phosphoric acid groups can form stable chelates with heavy metal ions through coordination, reducing the bioavailability of heavy metals; sulfonic acid groups can increase the cation exchange capacity of the material, reducing the leaching loss of readily available nutrients; and hydroxyl and amide groups help promote the formation of water-stable soil aggregates. The synergistic effect of these multiple functional groups achieves multiple benefits, including heavy metal passivation, nutrient retention, and improvement of soil physical properties.

[0025] 3. This invention scientifically blends modified dolomite and attapulgite, utilizing the complementary properties of their different crystal structures and functional characteristics. The one-dimensional rod-like structure of attapulgite and the core-shell structure of modified dolomite interweave to form a multi-level porous network, which helps improve the soil's water and fertilizer retention capacity and aeration. Simultaneously, the blended system can appropriately reduce the proportion of highly active modifying minerals while ensuring comprehensive improvement effects, helping to control product costs and making it more suitable for large-scale farmland application.

[0026] 4. This invention employs a low-temperature granulation and drying process for composite functional microbial agents, avoiding the damage to microbial activity caused by high-temperature treatment. The copolymer layer on the modified dolomite surface can buffer pH fluctuations on the mineral surface, and the microporous structure of attapulgite can also provide a certain degree of physical protection for microorganisms, helping to improve the survival rate and colonization ability of beneficial bacteria in the soil. The surviving beneficial microorganisms can continuously activate insoluble nutrients in the soil and inhibit some soil-borne diseases, achieving a synergistic improvement in the physical, chemical, and biological properties of the soil. Detailed Implementation

[0027] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] In the following examples and comparative examples, dolomite and natural attapulgite ore were both non-metallic mineral ores, prepared by crushing, pulverizing, grading and sieving; γ-methacryloyloxypropyltrimethoxysilane (KH-570, CAS No.: 2530-85-0) was industrial grade with a purity ≥98.0%; ethyl methacrylate phosphate (CAS No.: 24599-21-1), sodium vinyl sulfonate (CAS No.: 3039-83-6), and N-(2-hydroxyethyl)acrylamide (CAS No.: 7646-67-5) were all analytical grade with a purity ≥98.0%; ammonium persulfate and potassium persulfate were analytical grade with a purity ≥99.5%; Bacillus subtilis, Bacillus licheniformis, and Bacillus spp. were all commercially available agricultural strains.

[0029] Example 1

[0030] A method for preparing a mineral-based composite soil conditioner includes the following steps:

[0031] S1. Crush 100g of dolomite, pass it through a 100-mesh sieve, add 500mL of 0.05mol / L hydrochloric acid solution to remove impurities, acid wash for 1h, wash with deionized water until the filtrate is neutral, place it in an 80℃ oven to dry for 4h, and obtain 94g of pretreated dolomite powder.

[0032] S2. Add 94g of pretreated dolomite powder to 750mL of acidic ethanol aqueous solution with pH 3.5, wherein the volume fraction of ethanol is 80%, stir and disperse for 15min, add 1.9g of γ-methacryloyloxypropyltrimethoxysilane, heat to 55℃, and keep the reaction at this temperature for 2h to obtain activated dolomite.

[0033] S3. Nitrogen gas is introduced into the reactor. Activated dolomite is added to 940 mL of deionized water and stirred for 20 min. Then, 4.2 g of ethyl methacrylate, 2.1 g of sodium vinyl sulfonate, 3.1 g of N-(2-hydroxyethyl)acrylamide, and 0.05 g of ammonium persulfate are added sequentially. The temperature is raised to 65 °C and the copolymerization reaction is maintained at this temperature for 3 h. The product is washed three times with deionized water, filtered, dried, and ground to obtain modified dolomite.

[0034] S4. Take 65g of modified dolomite and 30g of natural attapulgite powder that has passed through a 200-mesh sieve, place them in a mixer and dry mix at 100rpm for 10min. Then add 0.5g of compound microbial agent, with a live bacteria ratio of Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosus of the same species of 2:1:1, and a total live bacteria count of 2.0×10⁻⁶. 9The mixture was prepared at CFU / g and mixed at 50 rpm for 5 minutes. Deionized water was sprayed to adjust the material moisture content to 15%. The mixture was then transferred to a disc granulator and the disc speed was controlled at 25 rpm to produce spherical particles with a particle size of 2 mm. The particles were then fed into a fluidized bed dryer and dried at 40°C for 2 hours to obtain the finished product.

[0035] Example 2

[0036] A method for preparing a mineral-based composite soil conditioner includes the following steps:

[0037] S1. Crush 100g of dolomite, pass it through a 150-mesh sieve, add 700mL of 0.12mol / L hydrochloric acid solution to remove impurities, acid wash for 2h, wash with deionized water until the filtrate is neutral, place it in a 90℃ oven to dry for 6h, and obtain 92g of pretreated dolomite powder.

[0038] S2. Add 92g of pretreated dolomite powder to 920mL of acidic ethanol aqueous solution with pH 4.0, wherein the volume fraction of ethanol is 88%, stir and disperse for 22min, add 3.2g of γ-methacryloyloxypropyltrimethoxysilane, heat to 60℃, and keep the reaction for 3h to obtain activated dolomite.

[0039] S3. Nitrogen gas is introduced into the reactor. Activated dolomite is added to 1100 mL of deionized water and stirred for 30 min. Then, 4.3 g of ethyl methacrylate, 2.2 g of sodium vinyl sulfonate, 3.2 g of N-(2-hydroxyethyl)acrylamide, and 0.1 g of potassium persulfate are added sequentially. The temperature is raised to 70 °C and the copolymerization reaction is maintained at this temperature for 4 h. The product is washed three times with deionized water, filtered, dried, and ground to obtain modified dolomite.

[0040] S4. Take 72g of modified dolomite and 26g of natural attapulgite powder that has passed through a 250-mesh sieve, place them in a mixer and dry mix at 150rpm for 15min. Then add 1.2g of compound microbial agent, with a live bacteria ratio of Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosa of the same species of 3:2:1, and a total live bacteria count of 3.0×10⁻⁶. 9 The mixture was prepared at CFU / g and mixed at 75 rpm for 7 minutes. Deionized water was sprayed to adjust the material moisture content to 20%. The mixture was then transferred to a disc granulator and the disc speed was controlled at 30 rpm to produce spherical particles with a particle size of 3 mm. The particles were then fed into a fluidized bed dryer and dried at 48°C for 3 hours to obtain the finished product.

[0041] Example 3

[0042] A method for preparing a mineral-based composite soil conditioner includes the following steps:

[0043] S1. Crush 100g of dolomite, pass it through a 200-mesh sieve, add 1000mL of 0.2mol / L hydrochloric acid solution to remove impurities, acid wash for 3h, wash with deionized water until the filtrate is neutral, place it in an oven at 105℃ and dry for 8h to obtain 90g of pretreated dolomite powder.

[0044] S2. Add 90g of pretreated dolomite powder to 1080mL of acidic ethanol aqueous solution with pH 4.5, wherein the volume fraction of ethanol is 95%, stir and disperse for 30min, add 4.5g of γ-methacryloyloxypropyltrimethoxysilane, heat to 65℃, keep warm for 4h, and obtain activated dolomite.

[0045] S3. Argon gas is introduced into the reactor. Activated dolomite is added to 1350 mL of deionized water and stirred for 40 min. Then, 4.4 g of ethyl methacrylate, 2.2 g of sodium vinyl sulfonate, 3.4 g of N-(2-hydroxyethyl)acrylamide and 0.15 g of ammonium persulfate are added sequentially. The temperature is raised to 75 °C and the copolymerization reaction is maintained at this temperature for 5 h. The product is washed three times with deionized water, filtered, dried, and ground to obtain modified dolomite.

[0046] S4. Take 80g of modified dolomite and 20g of natural attapulgite powder that has passed through a 300-mesh sieve, place them in a mixer and dry mix at 200rpm for 20min. Then add 2.0g of compound microbial agent, with a live bacteria ratio of Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosa of 4:3:1, and a total live bacteria count of 4.0×10⁻⁶. 9 The mixture was prepared at CFU / g and mixed at 100 rpm for 10 minutes. Deionized water was sprayed to adjust the material moisture content to 25%. The mixture was then transferred to a disc granulator and the disc speed was controlled at 35 rpm to produce spherical particles with a particle size of 4 mm. The particles were then fed into a fluidized bed dryer and dried at 55°C for 4 hours to obtain the finished product.

[0047] Example 4

[0048] A method for preparing a mineral-based composite soil conditioner includes the following steps:

[0049] S1. 100g of dolomite was crushed, passed through a 120-mesh sieve, and then acid-washed with 600mL of 0.08mol / L hydrochloric acid solution for 2.5h to remove impurities. The mixture was then washed with deionized water until the filtrate was neutral and dried in a 95℃ oven for 5h to obtain 93g of pretreated dolomite powder.

[0050] S2. Add 93g of pretreated dolomite powder to 840mL of acidic ethanol aqueous solution with pH 3.7, wherein the volume fraction of ethanol is 92%, stir and disperse for 20min, add 2.8g of γ-methacryloyloxypropyltrimethoxysilane, heat to 58℃, and keep the reaction at this temperature for 3.5h to obtain activated dolomite.

[0051] S3. Nitrogen gas is introduced into the reactor. Activated dolomite is added to 1020 mL of deionized water and stirred for 25 min. Then, 4.1 g of ethyl methacrylate, 2.1 g of sodium vinyl sulfonate, 3.3 g of N-(2-hydroxyethyl)acrylamide, and 0.08 g of potassium persulfate are added sequentially. The temperature is raised to 68 °C and the copolymerization reaction is maintained at this temperature for 4.5 h. The product is washed three times with deionized water, filtered, dried, and ground to obtain modified dolomite.

[0052] S4. Take 70g of modified dolomite and 29g of natural attapulgite powder that has passed through a 220-mesh sieve, place them in a mixer and dry mix at 120rpm for 12min. Then add 1.0g of compound microbial agent, with a live bacteria ratio of Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosa of the same species of 2.5:1.5:1, and a total live bacteria count of 2.5×10⁻⁶. 9 The mixture was prepared at CFU / g and mixed at 60 rpm for 8 minutes. Deionized water was sprayed to adjust the material moisture content to 18%. The mixture was then transferred to a disc granulator and the disc speed was controlled at 28 rpm to produce spherical particles with a particle size of 3 mm. The particles were then fed into a fluidized bed dryer and dried at 45°C for 3.5 hours to obtain the finished product.

[0053] Example 5

[0054] A method for preparing a mineral-based composite soil conditioner includes the following steps:

[0055] S1. Crush 100g of dolomite, pass it through a 180-mesh sieve, add 800mL of 0.15mol / L hydrochloric acid solution to remove impurities, acid wash for 2h, wash with deionized water until the filtrate is neutral, place it in a 100℃ oven to dry for 5h, and obtain 91g of pretreated dolomite powder.

[0056] S2. Add 91g of pretreated dolomite powder to 910mL of acidic ethanol aqueous solution with pH 4.2, wherein the volume fraction of ethanol is 90%, stir and disperse for 25min, add 3.3g of γ-methacryloyloxypropyltrimethoxysilane, heat to 62℃, and keep the reaction at this temperature for 3h to obtain activated dolomite.

[0057] S3. Nitrogen gas is introduced into the reactor. Activated dolomite is added to 1180 mL of deionized water and stirred for 35 min. Then, 4.2 g of ethyl methacrylate, 2.0 g of sodium vinyl sulfonate, 3.1 g of N-(2-hydroxyethyl)acrylamide, and 0.11 g of ammonium persulfate are added sequentially. The temperature is raised to 72 °C and the copolymerization reaction is maintained at this temperature for 4 h. The product is washed three times with deionized water, filtered, dried, and ground to obtain modified dolomite.

[0058] S4. Take 75g of modified dolomite and 24g of natural attapulgite powder that has passed through a 280-mesh sieve, place them in a mixer and dry mix at 180rpm for 18min. Then add 1.5g of compound microbial agent with a live bacteria ratio of Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosa at 3.5:2.5:1, for a total live bacteria count of 3.5×10⁻⁶. 9 The mixture was prepared at CFU / g and mixed at 80 rpm for 8 minutes. Deionized water was sprayed to adjust the material moisture content to 22%. The mixture was then transferred to a disc granulator and the disc speed was controlled at 32 rpm to produce spherical particles with a particle size of 3 mm. The particles were then fed into a fluidized bed dryer and dried at 50°C for 3 hours to obtain the finished product.

[0059] Example 6

[0060] A method for preparing a mineral-based composite soil conditioner includes the following steps:

[0061] S1. 100g of dolomite was crushed, passed through a 140-mesh sieve, and then 700mL of 0.1mol / L hydrochloric acid solution was added for acid washing to remove impurities. The acid washing time was 1.5h. The powder was washed with deionized water until the filtrate was neutral. The powder was then placed in an oven at 85℃ and dried for 7h to obtain 93g of pretreated dolomite powder.

[0062] S2. Add 93g of pretreated dolomite powder to 840mL of acidic ethanol aqueous solution with pH 3.8, wherein the volume fraction of ethanol is 85%, stir and disperse for 18min, add 2.3g of γ-methacryloyloxypropyltrimethoxysilane, heat to 57℃, and keep the reaction at this temperature for 2.5h to obtain activated dolomite.

[0063] S3. Argon gas is introduced into the reactor. Activated dolomite is added to 1020 mL of deionized water and stirred for 28 min. Then, 4.0 g of ethyl methacrylate, 2.0 g of sodium vinyl sulfonate, 3.0 g of N-(2-hydroxyethyl)acrylamide, and 0.06 g of potassium persulfate are added sequentially. The temperature is raised to 67 °C and the copolymerization reaction is maintained at this temperature for 3.5 h. The product is washed three times with deionized water, filtered, dried, and ground to obtain modified dolomite.

[0064] S4. Take 68g of modified dolomite and 30g of natural attapulgite powder that has passed through a 240-mesh sieve, place them in a mixer and dry mix at 130rpm for 14min. Then add 1.0g of compound microbial agent, with a live bacteria ratio of Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosa of the same species of bacteria ... 9 The mixture was prepared at CFU / g and mixed at 65 rpm for 6 minutes. Deionized water was sprayed to adjust the material moisture content to 17%. The mixture was then transferred to a disc granulator and the disc speed was controlled at 27 rpm to produce spherical particles with a particle size of 2 mm. The particles were then fed into a fluidized bed dryer and dried at 42°C for 2.5 hours to obtain the finished product.

[0065] Comparative Example 1

[0066] The difference from Example 1 is that step S1 does not involve acid washing to remove impurities with hydrochloric acid. Instead, 100g of dolomite is crushed and passed through a 100-mesh sieve and then directly placed in an 80°C oven to dry for 4 hours to obtain dolomite powder. Subsequent steps are the same as in Example 1.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that γ-methacryloyloxypropyltrimethoxysilane is not added in step S2, while the other steps are the same as in Example 1.

[0069] Comparative Example 3

[0070] The difference from Example 1 is that in step S3, ethyl methacrylate, sodium vinyl sulfonate, N-(2-hydroxyethyl)acrylamide and initiator are not added. The activated dolomite is directly washed, dried and ground and then used in subsequent steps. The remaining steps are the same as in Example 1.

[0071] Comparative Example 4

[0072] The difference from Example 1 is that in step S3, only 4.2g of ethyl methacrylate is added, and sodium vinyl sulfonate and N-(2-hydroxyethyl)acrylamide are not added. The amount of initiator remains unchanged, and the remaining steps are the same as in Example 1.

[0073] Comparative Example 5

[0074] The difference from Example 1 is that attapulgite powder is not added in step S4, and 95g of modified dolomite is mixed with 0.5g of composite microbial agent. The remaining steps are the same as in Example 1.

[0075] Comparative Example 6

[0076] The difference from Example 1 is that in step S4, no compound microbial agent is added. Instead, 65g of modified dolomite and 30g of attapulgite powder are mixed and then directly granulated and dried. The remaining steps are the same as in Example 1.

[0077] Topsoil (0-20cm depth) from an acidified farmland that has been used for long-term vegetable cultivation was collected. After air drying, stones, plant debris, and roots were removed. The soil was then crushed with a wooden stick, passed through a 2mm nylon sieve, and thoroughly mixed before use. The initial physicochemical properties of the soil were measured as follows: pH 4.82, cation exchange capacity 8.47 cmol / kg, organic matter content 12.28 g / kg, available nitrogen 52.06 mg / kg, available phosphorus 7.78 mg / kg, available potassium 68.37 mg / kg, DTPA-extractable cadmium 0.318 mg / kg, and DTPA-extractable lead 45.57 mg / kg.

[0078] Thirteen treatment groups were set up: a blank control group (CK, without any amendments), Examples 1-6, and Comparative Examples 1-6. Each treatment group was replicated in triplicate using a completely randomized block design. The test crop was Chinese cabbage (Brassicarapa L. ssp. chinensis), variety Shanghai Qing, and the seeds were purchased from the Institute of Vegetables and Flowers, Chinese Academy of Agricultural Sciences.

[0079] Weigh 1,000 kg of air-dried soil sample (passed through a 2 mm sieve) and place it in a plastic basin with an inner diameter of 15 cm and a height of 12 cm. Add the appropriate soil amendment sample at 0.5% of the soil dry weight and mix thoroughly with a glass rod. Add deionized water to adjust the soil moisture content to 60% of field capacity (i.e., add 180 g of water per kilogram of soil), weigh and record the result. Place all plastic basins in a 25°C constant temperature incubator in the dark. Weigh the soil every two days during the incubation period and replenish any water lost through evaporation to maintain a stable soil moisture content of 60% ± 2% of field capacity.

[0080] Destructive sampling was conducted on days 30, 90, and 180 of cultivation. Each replicate yielded approximately 200g of soil sample, which was divided into two parts: one part was stored in a 4°C refrigerator for determining the viable count of soil microorganisms; the other part was air-dried, ground, and sieved for determining the physicochemical properties of the soil.

[0081] On day 180 of cultivation, 10 plump, uniformly sized bok choy seeds were evenly sown in each plastic pot at a depth of approximately 0.5 cm. Seven days after emergence, thinning was performed, leaving 5 strong, uniformly growing seedlings per pot. During cultivation, the soil moisture content was maintained at 60% of field capacity, and no fertilizers or pesticides were applied. The bok choy was harvested after 30 days of growth, and crop growth indicators and heavy metal content in the above-ground parts were measured.

[0082] (1) Soil pH measurement

[0083] The potentiometric method was used, referring to the NY / T1121.2-2006 standard. 10.00 g of air-dried soil sample (passed through a 2 mm sieve) was weighed into a 50 mL plastic beaker, and 25 mL of carbon dioxide-free deionized water was added. The mixture was stirred with a glass rod for 1 min to ensure thorough dispersion. After standing for 30 min, the pH value of the supernatant was measured using a calibrated PHS-3C pH meter. Each sample was measured three times, and the average value was taken.

[0084] (2) Determination of soil cation exchange capacity (CEC)

[0085] The ammonium acetate exchange method was used according to the NY / T1121.5-2006 standard. 2.00 g of air-dried soil sample (passed through a 2 mm sieve) was weighed into a 50 mL centrifuge tube, and 20 mL of 1 mol / L ammonium acetate solution (pH 7.0) was added. The tube was placed on a constant-temperature shaking incubator and shaken at 200 rpm for 30 min, followed by centrifugation at 3000 rpm for 5 min. The supernatant was discarded. This step was repeated three times to ensure complete exchange of cations in the soil.

[0086] Add 20 mL of 95% ethanol to a centrifuge tube, shake for 5 min, centrifuge at 3000 rpm for 5 min, discard the supernatant, and repeat the washing process 3 times until no ammonium ions are present in the wash solution (test with Nessler's reagent; no yellow precipitate should form). Add 20 mL of 1 mol / L potassium chloride solution to the centrifuge tube, shake at 200 rpm for 30 min, centrifuge at 3000 rpm for 5 min, and carefully transfer the supernatant to a 100 mL Kjeldahl nitrogen determination flask. Wash the centrifuge tube twice with a small amount of 1 mol / L potassium chloride solution, 5 mL each time, and transfer the washings to the Kjeldahl nitrogen determination flask. Add 10 mL of 40% sodium hydroxide solution to the Kjeldahl nitrogen determination flask, immediately connect the Kjeldahl nitrogen determination distillation apparatus, and heat for distillation. Absorb the distillate in a 150 mL Erlenmeyer flask containing 20 mL of 2% boric acid solution (with 5 drops of methyl red-bromocresol green mixed indicator). Stop distillation when the volume of the distillate reaches 50 mL. Titrate the absorbent solution with 0.05 mol / L hydrochloric acid standard solution until the solution changes from blue to slightly pink, which is the endpoint. Record the volume of hydrochloric acid standard solution used. Perform a blank experiment at the same time.

[0087] Cation exchange capacity (CEC) is calculated using the following formula:

[0088] CEC(cmol / kg)=(V-V0)×c×1000 / m.

[0089] In the formula: V is the volume of hydrochloric acid standard solution consumed in the sample titration, in mL; V0 is the volume of hydrochloric acid standard solution consumed in the blank titration, in mL; c is the concentration of hydrochloric acid standard solution, in mol / L; m is the mass of the soil sample, in g.

[0090] (3) Determination of soil water-stable aggregate structure

[0091] The wet sieving method was adopted according to the NY / T1121.19-2008 standard. 50.00g of air-dried soil sample that had passed through a 2mm sieve was weighed and evenly spread on the top of a sieve set. The sieve sets, from top to bottom, consisted of 2mm, 0.25mm, and 0.053mm sieves. The sieve set was placed in a bucket of water, and water was slowly added until the water level was 1cm above the top sieve. The sample was soaked for 10 minutes. The wet sieving apparatus was then started and vibrated up and down at a frequency of 30 times / min for 10 minutes with an amplitude of 3cm. After vibration, the sieve set was slowly lifted to drain excess water. The soil samples from each sieve were rinsed into aluminum boxes of known mass and dried in an oven at 105℃ until constant weight. The samples were then weighed.

[0092] The mass fraction (WSA) of water-stable agglomerates with a particle size >0.25 mm is calculated using the following formula:

[0093] WSA(%)=(m 0.25 +m2) / m×100.

[0094] Where: m 0.25 m1 represents the dry weight of soil samples passing through a 0.25-2mm sieve, in g; m2 represents the dry weight of soil samples passing through a >2mm sieve, in g; m represents the total dry weight of the soil sample, in g.

[0095] (4) Determination of soil saturated water holding capacity

[0096] The ring cutter method was adopted, according to the NY / T1121.4-2006 standard. A volume of 100 cm³ was used. 3 Uncirculated soil samples were collected using a ring cutter. After being brought back to the laboratory, filter paper was placed under the ring cutter, and it was placed in a tray filled with deionized water, with the water level not exceeding the top edge of the ring cutter. The sample was soaked for 24 hours to allow the soil to fully absorb water and become saturated. The ring cutter was then removed, the outer wall was wiped dry with a clean cloth, and it was weighed. Next, the ring cutter was placed on a tray lined with dry sand and left for 2 hours to allow the gravitational water in the soil to drain completely. It was then weighed again.

[0097] Soil saturated water holding capacity (SWC) is calculated using the following formula:

[0098] SWC(%)=(m1-m2-m0) / m2×100.

[0099] In the formula: m1 is the total mass of the cutter and soil sample after water absorption saturation, in g; m2 is the total mass of the cutter and soil sample after drainage, in g; m0 is the mass of the cutter, in g.

[0100] (5) Determination of available heavy metal content in soil

[0101] The DTPA extraction-atomic absorption spectrophotometry method was used according to GB / T23739-2009 standard. 10.00 g of air-dried soil sample (passed through a 2 mm sieve) was weighed into a 50 mL plastic centrifuge tube, and 20 mL of DTPA extraction solvent (pH 7.3) was added. The tube was placed on a constant-temperature shaking incubator at 25℃ and 200 rpm for 2 h, followed by centrifugation at 4000 rpm for 10 min. The supernatant was collected and filtered through a 0.45 μm microporous membrane. The filtrate was used to determine the cadmium and lead content using an AA-6300 atomic absorption spectrophotometer. Instrument operating parameters: cadmium wavelength 228.8 nm, lamp current 3 mA, slit width 0.5 nm; lead wavelength 283.3 nm, lamp current 5 mA, slit width 0.5 nm. A blank experiment was also performed.

[0102] (6) Determination of available nutrients in soil

[0103] Alkaline nitrogen hydrolysis: The alkaline hydrolysis diffusion method was used according to NY / T1121.6-2006 standard. 2.00 g of air-dried soil sample (passed through a 2 mm sieve) was weighed into the outer chamber of a diffusion dish, and 1 mL of 1 mol / L sodium hydroxide solution was added. 2 mL of 2% boric acid solution (with a mixed indicator) was added to the inner chamber. The diffusion dish was sealed and incubated at 40℃ for 24 h. After incubation, the absorbent solution in the inner chamber was titrated with 0.01 mol / L hydrochloric acid standard solution until a faint pink color appeared, and the amount of hydrochloric acid used was recorded.

[0104] Available phosphorus: The sodium bicarbonate extraction-molybdenum antimony colorimetric method was used according to NY / T1121.7-2014 standard. Weigh 5.00 g of air-dried soil sample (passed through a 2 mm sieve) into a 250 mL plastic bottle, add 100 mL of 0.5 mol / L sodium bicarbonate solution (pH 8.5), shake at 25℃ and 200 rpm for 30 min, and filter. Take 10 mL of the filtrate into a 50 mL volumetric flask, add 5 mL of molybdenum antimony colorimetric reagent, dilute to the mark, shake well, and let stand for 30 min. Measure the absorbance at 700 nm using a UV-Vis spectrophotometer to calculate the available phosphorus content.

[0105] Available potassium: The ammonium acetate extraction-flame photometric method was used according to NY / T1121.8-2006 standard. 5.00 g of air-dried soil sample (passed through a 2 mm sieve) was weighed into a 50 mL plastic centrifuge tube, and 50 mL of 1 mol / L ammonium acetate solution (pH 7.0) was added. The mixture was shaken at 25℃ and 200 rpm for 30 min, and then filtered. The potassium content of the filtrate was determined using a flame photometer, and the available potassium content was calculated.

[0106] (7) Determination of viable count of beneficial microorganisms in soil

[0107] The dilution plating method was used. 10.00 g of fresh soil sample was weighed into an Erlenmeyer flask containing 90 mL of sterile physiological saline, placed on a constant-temperature shaking shaker, and shaken at 200 rpm for 30 min to prepare 10...-1 Diluent. Then, using a sterile pipette, take 1 mL of 10... -1 Dilute the solution in a test tube containing 9 mL of sterile physiological saline, shake well, and prepare 10 mL of solution. -2 Diluent. And so on, prepare 10... -3 10 -4 10 -5 10 -6 Diluent.

[0108] Take 0.1 mL of 10 mL of each sample. -4 10 -5 10 -6 Dilute the solution and spread it onto nutrient agar plates, with three plates for each dilution. Invert the plates and incubate them at 37°C for 24-48 hours. Observe the colony morphology, count the colonies of Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosa, and calculate the total viable count.

[0109] (8) Measurement of crop growth indicators

[0110] After harvesting the bok choy, measure the height from the base of the stem to the tip of the tallest leaf using a ruler; this is the plant height. Weigh the fresh weight of the above-ground parts using an electronic balance. Then, place the sample in a 105℃ oven for 30 minutes to blanch, and then dry it at 75℃ until constant weight, weighing the dry weight of the above-ground parts.

[0111] The experimental results are shown in Table 1-4:

[0112] Table 1. Results of soil physicochemical properties, available heavy metals, readily available nutrients, and beneficial microorganisms in each group after 30 days of cultivation.

[0113]

[0114] Table 2. Results of soil physicochemical properties, available heavy metals, readily available nutrients, and beneficial microorganisms in each group after 90 days of cultivation.

[0115]

[0116] Table 3. Results of soil physicochemical properties, available heavy metals, readily available nutrients, and beneficial microorganisms in each group after 180 days of cultivation.

[0117]

[0118] Table 4. Growth indicators and heavy metal content in the aboveground parts of Chinese cabbage plants under different treatments.

[0119]

[0120] As shown in Tables 1-4, during the three culture cycles of 30d, 90d, and 180d in Examples 1-6, the soil pH, cation exchange capacity, proportion of >0.25mm water-stable aggregates, and saturated water holding capacity were significantly higher than those in the blank control group and the comparative groups. The available cadmium and lead content in the soil were significantly lower, while the available nitrogen, phosphorus, and potassium content and the number of viable beneficial microorganisms were generally better than those in the control group. Correspondingly, the plant height, aboveground fresh weight, and dry weight of pakchoi were higher, and the cadmium and lead accumulation in the plants was significantly lower. Among them, Example 2 showed the best performance in all test indicators among all experimental groups. This invention adopts a stepwise modification and compounding process, which involves dolomite acid washing to remove impurities and activation, silane covalent bridging, in-situ copolymerization of multifunctional monomers, and low-temperature bacterial loading and granulation with attapulgite compounding, to construct a covalently bonded core-shell hybrid structure of rigid dolomite core, silane transition layer, and multifunctional copolymer shell. Acid washing selectively removes impurities from the mineral surface and exposes a large number of surface hydroxyl active sites, removing the coating and barrier of impurities on acid-base buffer sites; silanes rely on Si-O-Ca and Si-O-Mg covalent bonds to connect inorganic minerals and organic polymers, replacing weak interactions and effectively preventing the leaching and dissolution of organic functional components in the soil water environment; the three types of monomers copolymerize to form a network polymer carrying phosphoric acid, sulfonic acid, and hydroxyl groups. Phosphoric acid groups fix heavy metals through bidentate coordination chelation, sulfonic acid groups increase cation exchange capacity to retain readily available nutrients, and hydroxyl groups associate with soil clay particles through molecular hydrogen bonds to promote the formation of stable aggregates; the interlacing of attapulgite one-dimensional rod crystals forms a multi-level porous system, optimizing the soil pore structure while providing physical protection for beneficial bacteria. The low-temperature molding process avoids high-temperature inactivation of Bacillus subtilis, enabling the complex microbial community to colonize for a long time and activate insoluble nutrients in the soil. Multiple microstructures work together to achieve long-term improvement.

[0121] The blank control group received no soil amendments throughout the cultivation period. During this period, the soil pH slowly decreased, the available heavy metals slightly increased, and the water-stable aggregates, saturated water holding capacity, and available nutrients gradually decreased. The Chinese cabbage exhibited the worst growth indicators and the highest heavy metal accumulation. This is because the original acidified soil lacked an exogenous carbonate buffer framework and functional coordination and hydrophilic functional groups. The inherent carbonates in the soil were continuously consumed by free hydrogen ions, resulting in a lack of active components for fixing heavy metals and improving soil aggregates. Furthermore, without the replenishment of exogenous beneficial microorganisms, insoluble mineral nutrients could not be converted into available nutrients, leading to the continuous degradation of soil matrix properties.

[0122] Comparative Example 1 omits the acid washing step; Comparative Example 2 does not add silane coupling agents; Comparative Example 3 discards all comonomers; Comparative Example 4 retains only a single phosphate monomer; Comparative Example 5 does not add attapulgite; and Comparative Example 6 does not add composite microbial agents. The absence of any key process or component will destroy the complete organic-inorganic hybrid microscopic system. Without acid washing, impurities block the active sites of minerals, hindering subsequent grafting modification reactions; without silane bridging, the organic modified components rely solely on physical adsorption and are easily lost and ineffective in the soil; incomplete functional groups cannot simultaneously address heavy metal passivation, nutrient retention, and soil aggregate improvement; without the multi-level pores of attapulgite, microorganisms lack a protective environment, leading to increased loss of viable bacteria; the absence of functional microbial communities results in the loss of the bio-activation of nutrients, ultimately causing a simultaneous decline in soil physicochemical regulation, heavy metal fixation, nutrient retention, and crop growth promotion.

[0123] In summary, this invention constructs an organic-inorganic core-shell hybrid structure through a preparation process involving dolomite acid washing and activation, silane covalent bridging, in-situ copolymerization of multiple functional groups, attapulgite compounding, and low-temperature loading of functional bacteria. This structure achieves comprehensive soil improvement through multiple interactions such as coordination, ion exchange, and hydrogen bonding.

[0124] In the description of this specification, the reference to terms such as "example," "various examples," etc., means that a specific feature, structure, material, or characteristic described in connection with that example or preparation is included in at least one example or preparation of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same example or preparation. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more examples or preparations.

[0125] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a mineral-based composite soil conditioner, characterized in that, Includes the following steps: S1. After crushing and sieving the dolomite, it is acid-washed with hydrochloric acid solution to remove impurities, washed until neutral, and dried to obtain pretreated dolomite powder. S2. Disperse the pretreated dolomite powder in an acidic ethanol aqueous solution, add γ-methacryloxypropyltrimethoxysilane to carry out a hydrolysis-condensation reaction to obtain activated dolomite; S3. Under inert gas protection, activated dolomite is dispersed in water, and ethyl methacrylate, sodium vinyl sulfonate, N-(2-hydroxyethyl)acrylamide and initiator are added to carry out copolymerization reaction. The product is washed, dried and ground to obtain modified dolomite. S4. Mix the modified dolomite and attapulgite powder evenly with dry, then add the compound microbial agent and mix. After adjusting the humidity, granulate and dry at low temperature to obtain the finished product.

2. The preparation method according to claim 1, characterized in that, In step S1, the concentration of the hydrochloric acid solution is 0.05-0.2 mol / L; In step S2, the pH of the acidic ethanol aqueous solution is adjusted to 3.5-4.5 using glacial acetic acid, and the volume fraction of ethanol is 80-95%.

3. The preparation method according to claim 1, characterized in that, In step S2, the amount of γ-methacryloxypropyltrimethoxysilane used is 2-5% of the mass of the pretreated dolomite powder, the temperature of the hydrolysis-condensation reaction is 55-65℃, and the reaction time is 2-4h.

4. The preparation method according to claim 1, characterized in that, In step S3, the initiator is selected from ammonium persulfate or potassium persulfate; the mass ratio of ethyl methacrylate, sodium vinyl sulfonate, and N-(2-hydroxyethyl)acrylamide is (3.8-4.2):(1.9-2.1):(2.8-3.2).

5. The preparation method according to claim 1, characterized in that, The temperature for the copolymerization reaction in step S3 is 65-75℃, and the reaction time is 3-5 hours.

6. The preparation method according to claim 1, characterized in that, In step S4, the compound microbial agent is prepared by mixing Bacillus subtilis, Bacillus licheniformis, and Bacillus mucilaginosa in a viable count ratio of (2-4):(1-3):1, with a total viable count of not less than 2.0 × 10⁻⁶. 9 CFU / g.

7. The preparation method according to claim 1, characterized in that, In step S4, a disc granulator is used for granulation, and the rotation speed of the disc is controlled at 25-35 rpm to produce spherical particles with a particle size of 2-4 mm.

8. The preparation method according to claim 1, characterized in that, In step S4, low-temperature drying is performed using a fluidized bed dryer, with the drying temperature controlled at 40-55℃, so that the final moisture content of the particles is reduced to below 8%.

9. A mineral-based composite soil conditioner prepared by the preparation method according to any one of claims 1-8, characterized in that, It is prepared from the following raw materials in parts by weight: Modified dolomite 65-80 parts, attapulgite powder 20-30 parts, compound microbial agent 0.5-2.0 parts.

Citation Information

Patent Citations

  • Mineral soil conditioner and preparation method thereof

    CN106281353A

  • Attapulgite / polyacrylic acid compound heavy metal absorbent and preparation method thereof

    CN106000356A

  • Preparation and application of dolomitic attapulgite soil improvement material

    CN114507532A